Digitalization of Tourism and the Role of Generation Z in Parepare City (An Analysis from the Perspective of New Media Cultural Participation Theory) - Asaad, Iwan; Unde, Andi Alimuddin; Mau, Muliadi; Sultan, M Iqbal (Palakka : Media and Islamic Communication, 2024)
The Parepare City Government's policy of positioning the city as an industry without smokestacks, as outlined in the city's vision 2018-2023, the development of the tourism sector as highly urgent. Alongside digital media determinism, there is opportunity to develop a smart city that implements a series of tourism developments through digitalization to increase tourist visits, with a tourism digitalization program through the contributions of Generation Z. Based on research findings, Parepare City Government has encouraged policies for the involvement of Generation Z through various policies, such as programs and budgets to encourage the involvement and competence of Parepare's Generation Z residents. They has a significant contribution to tourism development through the use of information and communication technology, including citizen journalism, social media platforms, and cultural events that converge with digital information, as part of the globalization of Parepare's tourism information based on new media. This aligns with theory proposed by Henry Jenkins that the presence of new media will encourage audiences to collectively take roles, including Generation Z. Hence, Generation Z contributes to the activities on social media platforms for disseminating tourism information about Parepare City. The digital space participation of Parepare's Generation Z acts both as followers and prosumers.